2019
DOI: 10.3390/molecules24173033
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Identification of Bioactive Peptides from Amaranth Seed Proteins (Amaranthus hypochondriacus spp.)

Abstract: Amaranthus hypochondriacus spp. is a commonly grown cereal in Latin America, known for its high protein content. The objective of this study was to separate and identify bioactive peptides found in amaranth seeds through enzymatically-assisted hydrolysis using alcalase and flavourzyme. Hydrolysis was carried out for each enzyme separately and compared to two-step continuous process where both enzymes were combined. The biological activity of the resulting three hydrolysates was analyzed, finding, in general, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 63 publications
(74 reference statements)
0
19
1
Order By: Relevance
“…Their results showed that action of both enzymes affords hydrolysates with high antioxidant, antithrombotic and antihypertensive activity. It should be noted that the values obtained by Ayala-Niño et al. (2019a) are not very different from those reported by other authors for hydrolysates with alcalase ( Fritz et al., 2011 ; Ramírez-Torres et al., 2017 ).…”
Section: Bioactive Peptides As Blood Pressure Regulatorscontrasting
confidence: 44%
See 1 more Smart Citation
“…Their results showed that action of both enzymes affords hydrolysates with high antioxidant, antithrombotic and antihypertensive activity. It should be noted that the values obtained by Ayala-Niño et al. (2019a) are not very different from those reported by other authors for hydrolysates with alcalase ( Fritz et al., 2011 ; Ramírez-Torres et al., 2017 ).…”
Section: Bioactive Peptides As Blood Pressure Regulatorscontrasting
confidence: 44%
“… Ayala-Niño et al. (2019a) analyzed the profile of peptides obtained by the consecutive hydrolysis of a protein isolate from A. hypochondriacus with alcalase and flavourzyme.…”
Section: Bioactive Peptides As Blood Pressure Regulatorsmentioning
confidence: 99%
“…The antioxidant activities obtained in our study were lower than the antioxidant properties of cricket ( Amphiacusta annulipes ) protein hydrolyzed by gastrointestinal simulation, which presented IC 50 values of 19.1 and 7.4 µg/mL for the DPPH and ABTS radical scavenging activity, respectively (Zielińska, Karaś, & Jakubczyk, 2017). In contrast, the ABTS radical scavenging activity exhibited by the BCPC hydrolysate was higher than obtained for peptides from amaranth seed proteins that presented IC 50 ranging from 0.992 to 6.931 mg/mL (Ayala‐Niño et al., 2019).…”
Section: Resultsmentioning
confidence: 90%
“…This Special Issue has received remarkably positive feedback, with many contributions submitted by numerous geographically diverse scientists, resulting in a collection of 10 publications, including two exhaustive review articles [9][10][11][12][13][14][15][16][17][18]. Among the contributing authors, authors can be found from Asia (China, India, and Uzbekistan), Europe (Spain), South America (Brazil and Chile) and North America (Mexico).…”
mentioning
confidence: 99%
“…Another article described the multifunctional activity of amaranth (Amaranthus hypochondriacus spp.) proteins, opening the possibility that amaranth hydrolyzed with alcalase and flavourzyme to be used as a value-added ingredient with multi-functional bioactive properties [10]. Another article aimed to find an efficient extraction method and investigate some of physical and chemical parameters, like water solubility, emulsification, foaming properties, and oil-holding capacity of obtained scorpion proteins.…”
mentioning
confidence: 99%